ARCHITECT’S RESPONSE ON UTILISATION OF INTERLOCKING STABILISED SOIL BLOCKS AS AN ALTERNATIVE BUILDING MATERIAL FOR HOUSING PROJECTS IN SOUTHWEST NIGERIA (FUDMA JOURNAL OF SCIENCES, 2023)
Housing has become a major concern in Nigeria and requires sustainable intervention. The United Nations' position on the advantages of Interlocking Stabilised Soil blocks (ISSBs) in the year 2009 is fundamental to its usage for affordable housing delivery in developing nations. Considering the fact that the recent global economic challenges impacted the Nigerian economy, housing, recorded to be deficient by the Ministry of Housing in 2015 is a concern due to the tremendous rise in the cost of materials. This study assessed architects' response to the adoption of ISSBs as an alternative building material for Housing Projects in Southwest Nigeria towards recommending its widespread adoption for economical building construction works. The objectives were; to examine the role of architects in building material specifications; to explore characteristics of ISSBs that make them viable as an alternative building material, and to assess architects' response to the adoption of ISSBs. The study adopted a Mixed Method of Research in carrying out the assessment. Relevant literature was reviewed and necessary data were collected through interviews granted to the targeted respondents towards providing in-depth knowledge of ISSBs. Structured Questionnaires were administered to architects who are lecturers in selected schools of architecture who are members of the Association of Architectural Educators or registered with the Architects Registration Council of Nigeria. A total of 66 questionnaires were returned from the 70 administered. Findings revealed that architects have a huge role in building material specifications. ISSBs offer a passive solution to building challenges (better thermal comfort, quality indoor
Keywords: Building Cost; Economical Building Materials; Interlocking; Low-Cost Construction; Maintenance